Research funding and academic output: evidence from the Agricultural University of Athens. (1st September 2015) - Drivas, Kyriakos; Balafoutis, Athanasios T.; Rozakis, Stelios
Abstract : This paper uses detailed data on funding information and research output from the Agricultural University of Athens to examine how each type of funding source is related to the quantity and quality of academic research output. Of special interest are private, Greek government and European Union sources of funding. We find that after controlling for unobserved heterogeneity from each research laboratory, all types of research funding are similarly related to both the count of publications and citations. Further, we find that research laboratories that have filed for at least one patent application produce more publications and citations to their work, indicating that laboratories that are close to industry are also engaged actively in research.